Epsilon aminocaproic acid prevents bleeding in severely thrombocytopenic patients with hematological malignancies. Issue 21 (6th August 2013) - Antun, Ana G.; Gleason, Shannon; Arellano, Martha; Langston, Amelia A.; McLemore, Morgan L.; Gaddh, Manila; el Rassi, Fuad; Bernal‐Mizrachi, Leon; Galipeau, Jacques; Heffner, Leonard T.; Winton, Elliott F.; Khoury, Hanna J.
Abstract : BACKGROUND: Despite prophylactic platelet transfusions, bleeding remains a significant problem in thrombocytopenic patients. METHODS: The antifibrinolytic agent epsilon aminocaproic acid (EACA) was administered to 44 chronically (median duration, 273 days) and severely (platelet count, 8 × 10 9 /L; range, 1 × 10 9 /L‐ 19 × 10 9 /L) thrombocytopenic patients with hematological malignancies. Prophylactic EACA at a dose of 1 g twice daily was orally administered for a median duration of 47 days (range, 7 days‐209 days) until the platelet count recovered to > 30; × 10 9 /L. Platelets were only transfused if bleeding occurred. RESULTS: While receiving EACA, 59% of the patients did not bleed, 25% had 19 episodes of spontaneously resolving minor bleeding that did not require platelet transfusion, and 16% received a median of 4 platelet transfusions (range, 1 transfusion‐8 transfusions) for 1 major traumatic and 9 spontaneous grade 2 to grade 3 bleeding (based on the World Health Organization classification of idiopathic thrombocytopenic purpura). No EACA toxicities were noted, and venous thromboses were not observed. CONCLUSIONS: EACA is well tolerated and is associated with a low risk of major bleeding in patients with hematological malignancies who are experiencing chronic severe thrombocytopenia. Cancer 2013;119:3784–3787. © 2013 American Cancer Society. Abstract : Bleeding is a significant problem in thrombocytopenic patients with hematological malignancies. Epsilon aminocaproic acid is well‐tolerated and effective for bleeding prophylaxis in this patient population.